2016
DOI: 10.1016/j.heares.2016.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Differential tinnitus-related neuroplastic alterations of cortical thickness and surface area

Abstract: Structural neuroimaging techniques have been used to identify cortical and subcortical regions constituting the neuroarchitecture of tinnitus. One recent investigation used voxel-based morphometry (VBM) to analyze a sample of tinnitus patients (TI, n=257) [1]. A negative relationship between individual distress and cortical volume (CV) in bilateral auditory regions was observed. However, CV has meanwhile been identified as a neuroanatomical measurement that confounds genetically distinct neuroanatomical traits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 83 publications
(164 reference statements)
6
44
0
1
Order By: Relevance
“…The anatomical proximity of these regions indicates that the brain volume of the STG may serve as a neuroanatomical biomarker in differentiating patients with tinnitus from healthy subjects. Our results are also in line with those reported by Meyer et al, who examined a large and homogeneous sample of tinnitus patients [4]. This group also found that a decreased cortical volume in the left STG was closely related to tinnitus distress.…”
Section: Regions Of Altered Brain Volume In Patients Withsupporting
confidence: 93%
See 3 more Smart Citations
“…The anatomical proximity of these regions indicates that the brain volume of the STG may serve as a neuroanatomical biomarker in differentiating patients with tinnitus from healthy subjects. Our results are also in line with those reported by Meyer et al, who examined a large and homogeneous sample of tinnitus patients [4]. This group also found that a decreased cortical volume in the left STG was closely related to tinnitus distress.…”
Section: Regions Of Altered Brain Volume In Patients Withsupporting
confidence: 93%
“…The Tinnitus Handicap Inventory (THI) score was also acquired in the patient group to assess the severity of tinnitus and tinnitus-related distress. According to the score, tinnitus was divided into five levels: mild (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16), light (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36), moderate (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, several MRI and postmortem studies have reported remarkable interhemispheric differences with respect to HG morphology (Campain & Minckler, 1976;Chiarello, Kacinik, Manowitz, Otto, & Leonard, 2004;Dorsaint-Pierre et al, 2006;Galuske et al, 2000;Musiek & Reeves, 1990;Penhune et al, 1996;Penhune et al, 2003;Sigalovsky et al, 2006). However, recent studies have demonstrated that CTH and cortical surface area measurements should be considered to be independent neuroanatomical traits because CTH is distinct from cortical surface area in the contribution to cortical volume (Eyler et al, 2011;Greve et al, 2013;Meyer et al, 2014;Meyer et al, 2016;Panizzon et al, 2009;Winkler et al, 2010).…”
Section: Localization and Lateralization Of Pacmentioning
confidence: 99%